Accuracy of cytology, visual inspection with acetic acid or lugol’s iodine in cervical cancer screening - Khan, Samira; Jha, Rajshree; Pant, Pradam R (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aims: To study the accuracy of visual inspection using acetic acid (VIA) or Lugol's iodine (VILI) and Pap smear for cervical cancer screening comparing with the histology from positively screened women in all three. Method: In this descriptive study, 300 women 25 - 65 years from Gynecology clinic of T.U Teaching Hospital from December 2004 - 2005 underwent cervical screening. Positive tests for cytology was CIN I or above, VIA was opaque aceto white lesion on applying 4% acetic acid or detection of definite yellow iodine non uptake areas with Lugol's iodine in the transformation zone or close to touching the squamocolumnar junction. Positive cases were scheduled for colposcopy directed biopsies and histological evaluation. Results: Positive results obtained from cytology were 7.3% (22). VIA was positive in 52 women [low threshold +ve in 13.6% (41); high threshold +ve in 3.6%. (11)] VILI tested +ve in 8.7% (26). Cervical biopsy was done in 62 women who had positive result [10 were positive with all three tests, 4 were positive with VIA and Pap smear, 14 were positive with VIA and VILI. 24 were positive with only VIA, 2 were with only VILI and 8 were positive with only Pap smear]. Histology in 19 was suggestive of CIN and carcinoma. [LSIL (12), HSIL (6), carcinoma (1)] Pick up by Pap smear, VIA and VILI were 10; 17 and 15 missing respectively 9:[ LSIL (7) HSIL (2)]; [LSIL (2)] and 4 [LSIL (3) and HSIL (1)]. VIA had highest number of false positive as compared to Pap smear and VILI. Sensitivity for Pap smear (52.6%); low (81.1%)/high threshold VIA (80.0%) and VILI was (78.9%). Specificity for Pap smear (72 %); low was (20%) but high threshold VIA was similar to VILI (74.4%) The positive predictive value of low or high threshold VIA, VILI and cytology were 22.0%, 72.7%, 57.7% and 45.5%; such that the compounding NPV were 80.0%, 80.0%, 88.9% 77.5%. Overall accuracy of high threshold VIA (76 %) was comparable to VILI 75.8%; cytology having 66% and low threshold VIA with 33 %. Conclusion: High threshold VIA and VILI have higher accuracy for detection of precancerous lesions of cervix than Pap smear indicating that these test to be implicated for cancer screening which is more cost effective. Keywords: Visual inspection; acetic acid; Lugol's iodine; VIA; VILI; screening of cervical cancer; Papanicolau (Pap) smear. doi:10.3126/njog.v2i2.1455 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 48 - 53